Efficacy and Safety of 0.19-mg Fluocinolone Acetonide Implant in Postoperative Cystoid Macular Edema after Pars Plana Vitrectomy: The ILUvien in Postoperative CYstoid Macular eDema study - Motloch, Karolina; Soler, Vincent; Delyfer, Marie Noëlle; Vasseur, Vivien; Wolff, Benjamin; Issa, Mohamad; Dot, Corinne; Massé, Hélène; Weber, Michel; Comet, Alban; Hitzl, Wolfgang; Matonti, Frederic; et al. (Ophthalmology Retina, 2024)
Purpose: To assess the efficacy and safety of 0.19-mg fluocinolone acetonide (FAc) intravitreal implant (Iluvien) in treating chronic postoperative cystoid macular edema (PCME) after pars plana vitrectomy. Design: Retrospective multicentric case series in clinical settings. Subjects: Patients with chronic PCME who underwent vitrectomy in tertiary care centers in France. Methods: Review of charts and OCT scans. Main Outcome Measures: The primary end points were the best-corrected visual acuity (BCVA) and central retinal thickness (CRT). Secondary end points were the intraocular pressure (IOP); proportion of patients maintaining a BCVA ≥20/40; need for additional nonstudy treatment; differences between eyes that underwent a single and multiple surgeries; and OCT biomarkers of better BCVA. Results: Forty-nine eyes of 49 patients with a mean follow-up of 24.5 ± 3.87 months were included. The mean BCVA increased from 0.40 ± 0.26 logarithm of the minimum angle of resolution (logMAR) at baseline to 0.32 ± 0.24 logMAR at month 24 (P = 0.0035). The mean CRT decreased from 409 ± 139 μm at baseline to 340 ± 92 μm at month 24 (P = 0.0001). The mean IOP was 14.0 ± 4 mmHg at baseline and remained stable at 14.03 ± 4.1 mmHg at month 24 (P = 0.99). During the follow-up, the IOP exceeded 21 mmHg in 9 eyes, with one eye requiring cyclophotocoagulation. The BCVA was ≥20/40 in 47% of eyes (95% confidence interval [CI], 34%–61%) at baseline and in 58% of eyes at month 24 (95% CI, 41%–73%). At month 18, the likelihood of achieving a BCVA ≥20/40 was higher in eyes with intact external limiting membrane and ellipsoid zone. Additional dexamethasone (DEX) implant was injected in 14 eyes (28.6%). The treatment burden of 2.45 ± 1.35 DEX implant/y was decreased to 0.57 ± 0.60 DEX implant/y after FAc implantation (P = 0.001). Conclusions: Fluocinolone acetonide implant improved the BCVA, reduced the CRT, and allowed reducing treatment burden in eyes with chronic PCME after vitrectomy. The safety profile was acceptable. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Cystoid macular edema; Fluocinolone acetonide implant; Postoperative macular edema; Steroids; Vitrectomy